2021
DOI: 10.1051/0004-6361/201936456
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of galaxy scaling relations in clusters at 0.5 <z< 1.5

Abstract: Aims. We present new gas kinematic observations with the OSIRIS instrument at the GTC for galaxies in the Cl1604 cluster system at z ∼ 0.9. These observations together with a collection of other cluster samples at different epochs analyzed by our group are used to study the evolution of the Tully-Fisher, velocity-size, and specific angular momentum-stellar mass relations in dense environments over cosmic time. Methods. We used 2D and 3D spectroscopy to analyze the kinematics of our cluster galaxies and extract… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 145 publications
2
5
0
Order By: Relevance
“…Inclusion of such galaxies in a TFR analysis is expected to lead to a larger scatter and possibly zero point offsets in the TFR (see Section 8.1.1 on sample selection). At higher redshifts, several environment-specific TFR studies reported no significant differences in the TFRs in cluster and field populations (Ziegler et al 2003 ;Nakamura et al 2006 ;Jaff é et al 2011a ;P érez-Mart ínez et al 2021 ), while other studies such as Bamford et al ( 2005), Milvang-Jensen et al ( 2003, and P érez-Mart ínez et al ( 2021 , for z ∼ 1.5) found an o v erall brightening of cluster galaxies at a fixed rotational velocity. Other morphologyspecific studies such as Bedregal et al ( 2006 ) and Jaff é et al ( 2014 ) reported fainter magnitudes at a given rotational velocity for lenticular and early-type galaxies compared to spiral galaxies.…”
Section: The Tfrs From An Environmental Perspecti V Ementioning
confidence: 89%
“…Inclusion of such galaxies in a TFR analysis is expected to lead to a larger scatter and possibly zero point offsets in the TFR (see Section 8.1.1 on sample selection). At higher redshifts, several environment-specific TFR studies reported no significant differences in the TFRs in cluster and field populations (Ziegler et al 2003 ;Nakamura et al 2006 ;Jaff é et al 2011a ;P érez-Mart ínez et al 2021 ), while other studies such as Bamford et al ( 2005), Milvang-Jensen et al ( 2003, and P érez-Mart ínez et al ( 2021 , for z ∼ 1.5) found an o v erall brightening of cluster galaxies at a fixed rotational velocity. Other morphologyspecific studies such as Bedregal et al ( 2006 ) and Jaff é et al ( 2014 ) reported fainter magnitudes at a given rotational velocity for lenticular and early-type galaxies compared to spiral galaxies.…”
Section: The Tfrs From An Environmental Perspecti V Ementioning
confidence: 89%
“…Because physical mechanisms can affect the angular momentum of the baryons in different ways (i.e., increase or decrease it), an interpretation given in Pelliccia et al (2019) is that this reduction of angular momentum at a fixed stellar mass could be due to galaxy mergers, which is in line with their prevalence in dense environments (e.g., Tomczak et al 2019) and with recent simulations (e.g., Lagos et al 2018). However, the results from Pelliccia et al (2019) and Pérez-Martínez et al (2021) to compare galaxies from different surveys and observed with various instruments (e.g., Pérez-Martínez et al 2021) to reach these conclusions. As in Abril-Melgarejo et al (2021) and Mercier et al (2022), we argue that there might be systematic effects when doing so, mainly driven by different selection functions between different datasets.…”
Section: Introductionmentioning
confidence: 93%
“…Finally, a few studies have tried to probe the impact of the environment on the galaxies' angular momentum (e.g., Pelliccia et al 2019;Pérez-Martínez et al 2021). The current picture that emerges from these studies is that galaxies found in galaxy groups and galaxy clusters at z ∼ 1 seem to have a deficit of angular momentum with respect to field galaxies located at the same redshift.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrodynamical cluster-specific interactions between the interstellar medium (ISM) of galaxies and the intracluster medium (ICM) include ram pressure stripping (RPS, Gunn & Gott 1972), the removal of the hot halo gas (Larson et al 1980), as well as viscous stripping, and thermal evaporation (Cowie & Songaila 1977). These cluster-specific processes require different ambient conditions such as high ICM gas densities or low relative velocities between galaxies, imprinting specific features in the stellar and gas component of the cluster members, which can be observed, for example, in their light distribution (Hernández-Fernández et al 2012), structural parameters (Kuchner et al 2017), velocity fields (Pérez-Martínez et al 2017, Pérez-Martínez et al 2021, and oxygen abundances (Ciocan et al 2020, Maier et al 2022. Studies of intermediate redshift cluster galaxies also find evidence that environmental quenching not only depends on the ICM density, but also on the stellar mass of the galaxy, with less massive systems being more strongly affected by environmental mechanisms (e.g.…”
Section: Introductionmentioning
confidence: 99%